ENVIRONMENT PROTECTION UNDER THE ALBANIAN DOMESTIC LEGISLATION - Hitaj, Erjon (European Scientific Journal, ESJ, 2015)
Environment protection is of higher importance in developing countries like Albania. This paper shows how the new Albanian governmental and social bodies have faced this emerging challenge in favor both of the wellbeing and higher standards of environment of proper citizens. The rapid urban development which characterized the Albanian transition from the ’90s till nowadays has increasingly marked environmental standards. In addition, educational campaigns in favor of environmental protection have almost been absent although non-governmental agencies in the field are numerous. The awareness of the Albanian citizens at the beginning of the democratic processes towards issues of environment and sustainable development has been at the lowest ever; only with the improvement of economic standards and better quality of life, this sensibility towards the environment modified the fundamental social interests in favor of sustainable development without renouncing anyway from economic targets. The efforts of the government and the civil society in favor of the creation of a environmental mentality within the Albanian society is one of the clearest effects of the integration process towards the European Union which pays due attention to the environmental issues. The Albanian legislation, in the wake of the European one, tries to set up a complex of rules for the protection of environment under all its aspects. There is still much to do but the master route remains the European one.